Determinants of procedural pain intensity in the intensive care unit: the Europain® study - Puntillo, Kathleen A.; Max, Adeline; Timsit, Jean-Francois; Vignoud, Lucile; Chanques, Gerald; Gemma, Robleda; Roche-Campo, Ferran; Mancebo, Jordi; Divatia, Jigeeshu V.; Soares, Marcio; Ionescu, Daniela C.; Grintescu, Ioana M.; et al. (My University, 2014)
Rationale:Intensive care unit (ICU) patients undergo several diagnostic and therapeutic procedures every day. The prevalence, intensity, and risk factors of pain related to these procedures are not well known. Objectives: To assess self-reported procedural pain intensity versus baseline pain, examine pain intensity differences across procedures, and identify risk factors for procedural pain intensity. Methods: Prospective, cross-sectional, multicenter, multinational study of pain intensity associated with 12 procedures. Data were obtained from 3,851 patients who underwent 4,812 procedures in 192 ICUs in 28 countries. Measurements andMain Results: Painintensity on a 0–10 numeric rating scale increased significantly from baseline pain during all procedures (P , 0.001). Chest tube removal, wound drain removal, and arterial line insertion were the three most painful procedures, with median pain scores of 5 (3–7), 4.5 (2–7), and 4 (2–6), respectively. By multivariate analysis, risk factors independently associated with greater procedural pain intensity were the specific procedure; opioid administration specifically for the procedure; preprocedural pain intensity; preprocedural pain distress; intensity of the worst pain on the same day, before the procedure; and procedure not performed by a nurse. A significant ICU effect was observed, with no visible effect of country because of its absorption by the ICU effect. Some of the risk factors became nonsignificant when each procedure was examined separately. Conclusions: Knowledge of risk factors for greater procedural pain intensity identified in this study may help clinicians select interventions that are needed to minimize procedural pain. Clinical trial registered with www.clinicaltrials.gov (NCT 01070082).
Keywords: Symptom assessment; Analgesia; Prevention